FACTORS CAUSING RESPIRATORY TRACT COMPLAINTS IN SALON WORKERS IN JAMBI CITY IN 2022 - Devi Octafia; Cici Wuni; Novi Berliana (Jurnal Inovasi Penelitian, 2023)
Beauty salon workers are one of the professions with high risk, one of the health problems experienced by salon workers is respiratory tract complaints, respiratory tract complaints experienced by salon workers can be caused due to exposure to chemicals used when carrying out treatment to customers. The purpose of this study was to analyze the factors causing respiratory complaints in beauty salon workers in Jambi City. This research is a quantitative research with a cross-sectional approach. This research was conducted in Jambi City. The sample of this study was 41 beauty salon workers in Jambi City. The sample of this study was 41 beauty salon workers in Jambi City. The retrieval technique uses the Total Sampling technique. The instruments used are questionnaire sheets and measurements. Data collection techniques are carried out by interviews. The data were analyzed univariately and bivariately using the chi-square test. As many as 29.3% of respondents experienced respiratory complaints. Bivariate results showed no association between PPE use and respiratory tract complaints (P-value = 0,613), no relationship between length of work (P-value = 0,380), there is no relationship between service life (P-value = 0.427), no relationship between air vents (P-value = 0.378) to respiratory tract complaints. In conclusion, there is no relationship of variables of PPE use, length of service, length of service, and air ventilation to respiratory tract complaints in salon workers. It is recommended to beauty salon workers to always use PPE while working because there is exposure to chemicals that can cause respiratory complaints.